Design and Implementation of a Magnetic Levitation System Controller using Global Sliding Mode Control - Uswarman, Rudi; Cahyadi, Adha Iman; Wahyunggoro, Oyas (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2014)
This paper presents global sliding mode control and conventional sliding mode control for stabilization position of a levitation object. Sliding mode control will be robusting when in sliding mode condition. However, it is not necessarily robust at attaining phase. In the global sliding mode control, the attaining motion phase was eliminated, so that the robustness of the controller can be improved. However, the value of the parameter uncertainties needs to be limited. Besides that, the common problem in sliding mode control is high chattering phenomenon. If the chattering is too large, it can make the system unstable due the limited ability of electronics component. The strategy to overcome the chattering phenomenon is needed. Based on simulation and experimental results, the global sliding mode control has better performance than conventional sliding mode control.Â Â